2012
DOI: 10.1128/jvi.00722-12
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus 3C Protease Cleaves NEMO To Impair Innate Immune Signaling

Abstract: Foot-and-mouth disease is a highly contagious viral illness of wild and domestic cloven-hoofed animals. The causative agent, foot-and-mouth disease virus (FMDV), replicates rapidly, efficiently disseminating within the infected host and being passed on to susceptible animals via direct contact or the aerosol route. To survive in the host, FMDV has evolved to block the host interferon (IFN) response. Previously, we and others demonstrated that the leader proteinase (L pro ) of FMDV is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
136
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 61 publications
9
136
0
Order By: Relevance
“…Previous studies have reported that picornaviruses exert various strategies to evade host innate immune responses through certain viral proteins, such as L pro , VP2, VP3, 2A pro , 2C pro , 3A pro , and 3C pro (17,18,(25)(26)(27)(28)(29)(30)(31). In this study, we found that the overexpression of SVV proteins VP2, 3C pro , and 3D reduced Sev-induced IFN-␤ production (Fig.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies have reported that picornaviruses exert various strategies to evade host innate immune responses through certain viral proteins, such as L pro , VP2, VP3, 2A pro , 2C pro , 3A pro , and 3C pro (17,18,(25)(26)(27)(28)(29)(30)(31). In this study, we found that the overexpression of SVV proteins VP2, 3C pro , and 3D reduced Sev-induced IFN-␤ production (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Foot-and-mouth disease virus (FMDV) 3C pro and hepatitis A virus (HAV) 3C pro cleave NEMO to impair type I IFN production (30,31). Enterovirus 3C pro can target RIG-I, MAVS, TRIF, and IRF7 for cleavage to evade host antiviral innate immunity (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This also could explain the striking observation that acute HAV infection is associated with a very limited type I IFN response, despite the persistence of intrahepatic viral RNA (8). Previously, we reported that NEMO is a substrate for 3C pro of another picornavirus, foot-and-mouth disease virus (19). Recently, 3C…”
Section: Cmentioning
confidence: 91%
“…pro of foot-and-mouth disease virus cleaves NF-B essential modulator (NEMO) to impair innate immune signaling (40). The 3C pro precursors, 3ABC and 3CD, of hepatitis A virus cleave IPS-1 (41) and TRIF (42) to block antiviral signaling.…”
Section: Discussionmentioning
confidence: 99%